Determining a Piecewise Conductive Medium Body by a Single Far-Field Measurement (CSIAM Transactions on Applied Mathematics, 2020)
We are concerned with the inverse problem of recovering a conductivemedium body. The conductive medium body arises in several applications of practical importance, including the modelling of an electromagnetic object coated witha thin layer of a highly conducting material and the magnetotellurics in geophysics.We consider the determination of the material parameters inside the body as well ason the conductive interface by the associated electromagnetic far-field measurement.Under the transverse-magnetic polarisation, we derive two novel unique identifiability results in determining a 2D piecewise conductive medium body associated witha polygonal-nest or a polygonal-cell geometry by a single active or passive far-fieldmeasurement.
Keywords: Electromagnetic scattering; conductive transmission condition; inverse problem; single far-field measurement; polygonal; corner singularity.